Syntactic stylistic devices (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
This article gives information about Syntactic stylistic devices. In this article it has several paragraphs, which give full data about this. It is based on what is syntactic stylistic devices. In short, syntactic stylistic devices include inversion, indivisible structures, parallel devices, chiasm, repetition, ellipse, accent, counting, gradation, antithesis, and each of them performs a specific function. What is indivisible structures? What is the difference between chiasm and repetition? What is ellipse? In this article, candidates can learn how to be a good learner and what is stylistic devices and how to use it.